The Khan as 'Meta-Emperor' in Marco Polo's Devisement du Monde. (October 2017) - Pérez-Simon, Maud
Marco Polo's Le Devisement du Monde (end of the thirteenth century) is one of the earliest, longest and more detailed travelogues of the Middle Ages. Widely read, the text not only describes the travels of its protagonist, but equally furnishes a comprehensive overview of Mongolian culture, society and territories. This article analyses the categories Marco Polo uses in order to describe the Khan's realm and his exercise of power. The author rarely uses the notion of emperor in his narrative, although he clearly recognises the Khan's claim to universal rule. The reasons behind this reluctance can be explained in several ways. First, Marco Polo became acquainted with the main languages in the regions under Mongolian rule; it might thus have seemed natural to him to use the 'correct' titles. Second, the French vernacular word 'empire' might have been reserved, in his mind, for the rulers of the 'Roman Empire' (in the Latin West and/or the Greek East). Finally, it seems that Marco Polo sought to ascribe to the Khans a kind of power and authority that surpassed even the might of the emperors in Europe, and this specificity could best be expressed by using a Mongolian title that, finally, was not entirely synonymous with the notion of empereur. All in all, these observations imply that the Devisement du Monde can be read not only as a travel narrative, but also as a treatise on the understanding of imperial power.